Sr11Ge4N6: a new nitride composed of [GeN2Sr7]4+ antiperovskite-type slabs and [Sr4Ge]4+ layers, separated by sheets of bent [Ge(II)N2]4- ions. - Gál, Z; Clarke, S (2005)
The layered nitride Sr11Ge4N6 contains Ge4- Zintl anions in both [Sr4Ge]4+ layers and [GeN2Sr7]4+ antiperovskite-type slabs which are separated by sheets of bent [Ge(II)N2]4- ions; the observed range of formal germanium oxidation states in nitrides thus extends between +4 and -4.